Can metronomic maintenance with weekly vinblastine prevent early relapse/progression after bevacizumab–irinotecan in children with low‐grade glioma?. (31st March 2016) - Heng, Marie Amélie; Padovani, Laetitia; Dory‐Lautrec, Philippe; Gentet, Jean Claude; Verschuur, Arnaud; Pasquier, Eddy; Figarella‐Branger, Dominique; Scavarda, Didier; André, Nicolas
Abstract : Metronomic maintenance with vinblastine after irinotecan–bevacizumab induction may prevent relapse in children with low‐grade glioma. Abstract: The association of bevacizumab and irinotecan has been shown to display a quick efficacy in low‐grade glioma (LGG), but most patients relapse within months after cessation of therapy. From October 2012 to March 2014, four patients have been treated with irinotecan–bevacizumab followed by a metronomic maintenance with weekly vinblastine to try to prevent relapses. After a median follow‐up of 23 months after the end of the bevacizumab–irinotecan induction, no patient relapsed. These observations suggest that maintenance chemotherapy with weekly vinblastine after an induction by irinotecan–bevacizumab can improve progression‐free survival in children with LGG.